Students’ and teachers’ perceptions for composition of ionic compounds - Wisudawati Asih Widi; Barke Hans-Dieter; Lemma Abayneh; Agung Salamah (Chemistry Teacher International, 2022)
We investigate how chemistry-teacher students and teachers interpret chemical equations regarding the sub-microscopic level of solid ionic salts and their solutions. Addressing participants’ skills in making sense of chemical formulas might significantly influence students’ conceptual understanding: ionic salts formulas like Na2CO3(s), CaCO3(s), MgO(s) were established in the questionnaire. A coding system used to reveal participants’ reasoning correspond to their misconceptions. The enrolled participants were 101 undergraduate chemistry education students from Indonesia and Ethiopia and 24 chemistry teachers from Indonesia and Tanzania. Our results showed students’ and teachers’ difficulties in figuring out the involved ions of provided salts and interpreting the chemical formulas. Consequently, general chemistry learning should provide better fundamental knowledge on the submicroscopic level based on involved particles like atoms, ions, and molecules. It would also be helpful to introduce an appropriate sequence of historical ideas to find the existence of atoms, ions, and molecules.